Diversity, structure and carbon of the arboreal vegetation on cocoa agroforestry systems - Salvador-Morales, Pedro; Cámara-Cabrales, Luisa del Carmen; Martínez-Sánchez, José Luis; Sánchez-Hernández, Rufo; Valdés-Velarde, Eduardo (Instituto de Ecología, A.C., 2019)
The conservation of cocoa agroforestry systems (SAFC) in Tabasco, Mexico, requires the revaluation of their environmental functions, since they represent relicts of arboreal vegetation in a landscape dominated by cultivated areas. For this reason, a research was developed to evaluate the diversity, arboreal structure and carbon stored in the SAFC, according to age, soils and municipalities. For that, the SAFC were inventoried to determinate the diversity through the indexes Shannon-Wienner and Sorenson respectively, arboreal structure through the importance value index, diametric classes and height, as well as the aerial biomass estimated through allometric equations, with which the carbon contents were calculated. We identified 24 families, 37 genera and 39 species. The SAFC > 40 years have slightly more diversity and arboreal density. Based in the age of the SAFC, the arboreal diversity and structure is highest in the SAFC ≥ 40 years with respect to SAFC > 10 years - 15 years and SAFC > 20 years - 35 years; while as with respect to soil group, the aforementioned indicators are higher in the Gleysols, followed by the Fluvisols, Cambisols and Vertisols. The age and soil type determine the carbon stored in the aerial biomass. 75% and 25% of the C of aerial biomass is stored in shade trees and cocoa, respectively. It is concluded that the SAFCs in Tabasco are similar in diversity and tree structure. The older ones established in Fluvisols are slightly more diverse and register a larger basal area, so they store more C in the aerial biomass.